Equipping Mathematics Pre-Service Teachers for the Digital Classroom: Research on Tools, Pedagogies, and Instructional Design - Bernard Justus Wekullo; Romario Montano Ramos; Ana Huber Castillo (Scientia Publica Media, 2026)
This systematic literature review (SLR) synthesizes research published between 2014 and 2024 on preparing pre-service mathematics teachers (PSTs) for technology-enhanced classrooms. The study addresses the growing global expectation for teacher education programs to integrate digital tools and constructivist pedagogies while promoting equity and conceptual understanding in mathematics instruction. Despite these demands, PSTs often struggle to balance technological, pedagogical, and content knowledge, relying on traditional methods that limit authentic technology use. Guided by three research questions, the review examined: (a) how digital tools such as GeoGebra, 3D printing, and collaborative platforms influence PSTs’ mathematical understanding and real-world application; (b) how constructivist, technology-based strategies like flipped classrooms and peer learning affect engagement, confidence, and instructional planning; and (c) what factors shape PSTs’ ability to evaluate and integrate digital resources into student-centered, standards-aligned instruction. Using a rigorous SLR process across five major databases (Google Scholar, Scopus, Web of Science, ERIC, JSTOR), 24 peer-reviewed studies were analyzed through Garrard’s Matrix Method and thematic coding. Findings reveal that digital tools enhance representational fluency, problem-solving, and Technological Pedagogical Content Knowledge (TPACK), while constructivist approaches foster engagement, autonomy, and reflective practice. However, persistent challenges, such as inequitable access to technology, limited interdisciplinary training, and entrenched procedural teaching beliefs, constrain integration. Factors influencing adoption include pedagogical orientations, institutional support, and collaborative opportunities. The review concludes that the intentional, scaffolded integration of emerging technologies within constructivist frameworks strengthens PSTs’ readiness for 21st-century classrooms. However, the small sample of 24 articles and the exclusion of sources like gray literature limit the study’s generalizability. Nevertheless, the findings can guide teacher educators, curriculum designers, and education ministries in promoting equitable, technology-rich mathematics education through authentic digital inquiry and targeted professional development.